On the Runtime and Energy Performance of WebAssembly: Is WebAssembly superior to JavaScript yet? - De Macedo, Joao; Abreu, Rui; Pereira, Rui; Saraiva, Joao (2021 36th IEEE/ACM International Conference on Automated Software Engineering Workshops (ASEW), 2021)
In the early days of the world wide web, browsers were developed to navigate through (static) HTML web page documents. This has changed dramatically, and nowadays web pages are dynamic, expressed by programs written in regular programming languages. As a result, browsers are almost operating systems, having to interpret/compile such programs and execute them within the browser itself. Currently, while JavaScript is the main de facto language to express web pages, it does have various short comings and performance inefficiencies. WebAssembly, a new portable and size/load efficient alternative developed by major IT powerhouses, is seen as the future substitute. As WebAssembly aims to be more performance efficient than JavaScript, we aim to look at this current status and present a preliminary study on the performance of these two, based on their runtime and energy efficiency. Preliminary results show that WebAssembly, while still in its infancy, is starting to already challenge JavaScript, with much more room to grow. Additionally, our benchmarking framework is also made available to allow further research and replication.